An association between pulmonary hypertension and impaired lung function in infants with congenital diaphragmatic hernia. Issue 7 (13th March 2014) - Healy, Fiona; Lin, Wei; Feng, Rui; Hanna, Brian D.; Hedrick, Holly; Panitch, Howard B.
Summary Rationale Infants with congenital diaphragmatic hernia (CDH) can develop pulmonary hypertension (PH) from decreased number and abnormal muscularization of pulmonary arteries. Normally pulmonary vascular growth and remodeling parallel airspace growth and alveolarization, which exhibits a wide morphologic variation in CDH. Aim To assess whether infants with CDH and PH have greater abnormalities in infant pulmonary function testing (IPFT) compared to those without PH. Methods We reviewed results of IPFTs and echocardiograms performed on infants with CDH from 2004 to June 2011. Lung volumes, forced flows and tidal mechanics were standardized according to available reference values. Comparisons between infants with and without PH were performed using linear regression, adjusting for potential confounders. Main Results Sixty‐six infants were included; 18 had PH and 48 did not. Z‐score values for functional residual capacity (FRC), residual volume (RV), FRC/total lung capacity (TLC), and RV/TLC were significantly higher in infants with CDH and PH compared to those without PH. Z‐score values for forced flows including forced expiratory volume in the first 0.5 sec (FEV0.5) and FEV0.5/forced vital capacity were significantly lower in infants with CDH and PH compared to those without PH. For 29 infants studied on ≥2 occasions, the slopes of FRC, RV, and TLC versus length were significantly higher in those with persistent PH compared to those without. Conclusions Infants with CDH and persistent PH demonstrate greater airspace overdistension with growth compared to those without. Therapies that modify disrupted pulmonary vascular and alveolar formation could potentially improve future care of these patients. Pediatr Pulmonol. 2015; 50:672–682. © 2014 Wiley Periodicals, Inc.